2020
DOI: 10.1039/d0ra07861a
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of young shoots and the mature red headed cabbage as antioxidant food resources with antiproliferative effect on prostate cancer cells

Abstract: Young shoots of red cabbage could be a good source of phytochemicals with potential anticancer activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 68 publications
7
21
1
Order By: Relevance
“…It was, therefore, essential to determine their levels in this research. Past studies have reported on changes of the TPC content when seeds were germinated [19][20][21]. Previous studies have indicated that germination can gradually lead to TPC accumulation in germinated edible seeds by stimulating enzymes such as phenylalanine ammonia lyase (PAL), which plays key roles in the de novo pathways [10,19,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was, therefore, essential to determine their levels in this research. Past studies have reported on changes of the TPC content when seeds were germinated [19][20][21]. Previous studies have indicated that germination can gradually lead to TPC accumulation in germinated edible seeds by stimulating enzymes such as phenylalanine ammonia lyase (PAL), which plays key roles in the de novo pathways [10,19,22].…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids are the major types of phenolic compounds, which are useful in protecting against diabetes in humans, in addition to playing various key roles, such as protecting the plant against environmental stress [22]. Earlier, it was reported that germination improved TFC levels in broccoli [20] and red cabbage [21]. In contrast to these reports, our study revealed that germination significantly decreased the levels of TFC in red cabbage from 215.7 ± 0.16 to 209.9 ± 0.03 mg CE/100 g. Similarly, TFC levels in broccoli seeds significantly decreased upon germination from 216.9 ± 0.38 mg CE/100 g in raw seeds to 206.9 ± 0.02 mg CE/100 g in sprouts.…”
Section: Discussionmentioning
confidence: 99%
“…Baenas et al [ 26 ], who studied 4-day-old red cabbage sprouts, demonstrated a similar radical scavenging activity in DPPH and FRAP assays. Seven-day-old red cabbage sprouts showed a high antioxidant activity in FRAP and DPPH assay, but the results were lower in comparison to Drozdowska et al [ 42 ] data [ 43 ].…”
Section: Discussionmentioning
confidence: 64%
“…In a study by Drozdowska et al [ 42 ], the antioxidant activity of plant samples was determined using three methods: with ABTS˙ + , DPPH and FRAP reagents. The applied methods were adequate for the examined material—young shoots of red headed cabbage showed a higher radical scavenging activity in comparison to white headed headed cabbage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation